Respostas morfofisiológicas de cultivares de trigo em competição com azevém diploide e tetraploide - Baldessarini, Renata (2019)
Among the weeds that cause interference in the growth and development of wheat stands out ryegrass, in particular because it presents high competitive ability for the resources available in the environment. The objective of this work was to evaluate the competitive ability of wheat cultivars when living with two ryegrass biotypes. Experiments were installed in greenhouse, in the experimental design of randomized blocks, with four replications. The treatments were arranged in substitution series, constituted by proportions of ryegrass plants: 100:0, 75:25, 50:50, 25:75 e 0:100% equivalent 1, 2, 4, 8, 16, 24, 32, 40, 48, 56 e 64 pot plants-1 . The wheat was represented by the cultivars BRS Parrudo and TBIO Sinuelo and the competitors by diploid and tetraploid ryegrass. The competitiveness analysis was carried out through diagrams applied to substitutive experiments, plus use of relative competitiveness indexes. The stem diameter (DC), number of tiller (NP), dry mass (MS), photosynthetic activity (Afs), internal concentration of CO2 in mesophyll (Ci), carboxy efficiency (EC), leaf area (AF), perspiration (E), efficiency in water use (EUA) and stomatal conductance (Gs) were evaluated at 50 days after emergence of the species. The results demonstrate that there was competition between wheat cultivars with ryegrass with mutual injury to the species involved in the community. The ryegrass modified the AF and MS of cultivars BRS Parrudo and TBIO Sinuelo demonstrating superior competitive ability by means resources. Interspecific competition causes greater damage to FA and MS of species than intraspecific competition. Therefore, it is recommended to control ryegrass even when present at low plant densities infesting wheat.